Comparing hospital and telephone follow‐up for patients treated for stage–I endometrial cancer (ENDCAT trial): a randomised, multicentre, non‐inferiority trial. (7th April 2016) - Beaver, K; Williamson, S; Sutton, C; Hollingworth, W; Gardner, A; Allton, B; Abdel‐Aty, M; Blackwood, K; Burns, S; Curwen, D; Ghani, R; Keating, P; et al.
Abstract : Objective: To evaluate the effectiveness of nurse‐led telephone follow‐up (TFU) for patients with stage–I endometrial cancer. Design: Multicentre, randomised, non‐inferiority trial. Setting: Five centres in the North West of England. Sample: A cohort of 259 women treated for stage–I endometrial cancer attending hospital outpatient clinics for routine follow‐up. Methods: Participants were randomly allocated to receive traditional hospital based follow‐up (HFU) or nurse‐led TFU. Main outcome measures: Primary outcomes were psychological morbidity (State Trait Anxiety Inventory, STAI–S) and patient satisfaction with the information provided. Secondary outcomes included patient satisfaction with service, quality of life, and time to detection of recurrence. Results: The STAI–S scores post‐randomisation were similar between groups [mean (SD): TFU 33.0 (11.0); HFU 35.5 (13.0)]. The estimated between‐group difference in STAI–S was 0.7 (95% confidence interval, 95% CI −1.9 to 3.3); the confidence interval lies above the non‐inferiority limit (−3.5), indicating the non‐inferiority of TFU. There was no significant difference between groups in reported satisfaction with information (odds ratio, OR 0.9; 95% CI 0.4–2.1; P  = 0.83). Women in the HFU group were more likely to report being kept waiting for their appointment ( P  = 0.001), that they did not need any information ( P  = 0.003), and were less likely to report that the nurse knew about their particular case and situation ( P  = 0.005). Conclusions: The TFU provides an effective alternative to HFU for patients with stage–I endometrial cancer, with no reported physical or psychological detriment. Patient satisfaction with information was high, with similar levels between groups. Tweetable abstract: ENDCAT trial shows effectiveness of nurse‐led telephone follow‐up for patients with stage‐I endometrial cancer. Tweetable abstract: ENDCAT trial shows effectiveness of nurse‐led telephone follow‐up for patients with stage‐I endometrial cancer.